A More Important Role for the Ozone‐S(IV) Oxidation Pathway Due to Decreasing Acidity in Clouds. Issue 18 (18th September 2020) - Li, Jiarong; Zhu, Chao; Chen, Hui; Fu, Hongbo; Xiao, Hang; Wang, Xiaofei; Herrmann, Hartmut; Chen, Jianmin
Abstract: Clouds significantly affect the Earth's radiation budget and play a critical role in atmospheric sulfate formation. The pathways of S(IV) oxidations have recently caused a controversial attention under severe haze episodes due to the variable acidity and water content in aerosol particles. In this study, a total of 158 cloud samples were collected from 2014 to 2018 at the summit of Mt. Tai, China, to explore the roles of atmospheric oxidants in aqueous S(IV) oxidation. The results showed that the averaged pH value of cloud water increased dramatically from 3.86 (Guo et al., 2012, https://doi.org/10.1016/j.atmosenv.2012.07.016 ) in 2007–2008, 5.5 in 2014, to 6.4 in 2018, respectively, while water soluble secondary ions (SO4 2−, NO3 − and NH4 + ) and S(IV) decreased significantly. The four pathways of S(IV) oxidation by O3, H2 O2, NO2, and trace metal‐catalyzed autooxidation were further discussed, and the roles in S(IV) oxidation pathways were found changing significantly with pH value in clouds. The rate of H2 O2 pathway contributed about 95.8% for S(IV) oxidation when pH was less than 4.0. For pH around 5.0, the rate of O3 pathway became comparable with the H2 O2 pathway, and it accounted more than 95.2% for the total S(IV) oxidation rate when pH was larger than 6.0. Based on the long‐term field measurement, this study indicated that the high concentration of O3 and the increasing trend of pH promoted a shift of the dominant S(IV) oxidation from H2 O2 pathway in a previous study (Shen et al., 2012, https://doi.org/10.1016/j.atmosenv.2012.07.079 ) to O3 pathway in clouds. Key Points: The pH values of clouds significantly increased while secondary ions (SO4 2−, NO3 −, and NH4 + ) decreased over the years from 2007 to 2018 Cloud process played important roles in reducing O3 and SO2 in the air O3 pathway dominanted the S(IV) oxidation in cloud at Mt. Tai, which was attributed to the increased pH values